2023
DOI: 10.1186/s12889-023-16160-2
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of low birth weight to childhood undernutrition in India: evidence from the national family health survey 2019–2021

Abstract: Background Infants born with low birth weight (LBW), i.e. less than 2500g, is considered an important factor of malnutrition in Asia. In India, research related to this issue is still neglected and limited. Evidence exists that a large number of child deaths occur in India due to maternal and child malnutrition-related complications. Moreover, it has been found that the cost of malnutrition in India results in a significant reduction of the country's Gross Domestic Product (GDP). Thus, in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
(56 reference statements)
3
1
1
Order By: Relevance
“…This result is similar to the findings of previous research [33]. In our study, wasting was significantly linked to gestational age at birth of children which resonates with published evidence that has highlighted the effect of preterm birth and low birth weight on child growth and development [21,39]. Considering the heavy burden of childhood undernutrition in India, the identification of factors contributing to its persistence is important and the findings generated by our study would enrich the evidence base and provide direction for future intervention studies.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is similar to the findings of previous research [33]. In our study, wasting was significantly linked to gestational age at birth of children which resonates with published evidence that has highlighted the effect of preterm birth and low birth weight on child growth and development [21,39]. Considering the heavy burden of childhood undernutrition in India, the identification of factors contributing to its persistence is important and the findings generated by our study would enrich the evidence base and provide direction for future intervention studies.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found that approximately 51 (34.7%) of the studied children were stunted. Our findings are in line with the NFHS-5 (2019-2021), which reports that 32.77% and 32.55% of children in MP and all over India have stunting, respectively [21]. Stunting is reported to be the result of chronic inadequate maternal and child nutrition that can occur secondary to multiple factors ranging from socioeconomic status influenced by the parent's education/occupation to the child's medical history affected by recurrent infections, hospitalizations, or chronic diseases that lead to poor intake, absorption, and utilization of foods [27].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The association between LBW and weight gain observed in this study is consistent with the findings of the Aboagye studies in sub-Saharan Africa (OR = 1.82) [ 21 ], Arup Jana in India (OR = 1.76) [ 22 ], Khan in Pakistan (OR = 1.67) [ 13 ], and Asmare in The Gambia [ 23 ]. This association may be because LBW children are prone to infections such as diarrhea, prolonged hospitalization, inability to breastfeed, and loss of appetite, leading to poor physical growth and development [ 24 ].…”
Section: Discussionsupporting
confidence: 91%